Using Human-Centered Design to Bridge Zero-Dose Vaccine Gap: A Case Study of Ilala District in Tanzania - Simon Martin Nzilibili; Hellen Maziku; Awet Araya; Ruthbetha Kateule; Millenium Anthony Malamla; Suna Salum; Furaha Kyesi; Lotalis Gadau; Tumaini Menson Haonga; Florian Tinuga; Rashid Mfaume; Zaitun Hamza; et al. (Vaccines)
Background: Immunization plays a substantial role in reducing the under-five mortality rate. However, Tanzania still has a significant number of zero-dose and under-vaccinated children and was ranked among the top ten African countries with the highest numbers of zero-dose children in 2022. The human-centered design (HCD) approach is more ethical and effective at addressing public health challenges in complex sociocultural settings. This study aimed to use the HCD approach to aid in identifying, prioritizing, and implementing community-centric interventions in Tanzania, particularly in the Ilala District of Dar es Salaam, to increase vaccine demand and close the zero-dose gap by at least 50%. Methods: The study involved co-creation workshops with 483 participants to identify, design, and test solutions. The study followed the UNICEF Journey to Health and Immunization framework to identify barriers and enablers influencing stakeholders in adopting and sustaining health- and immunization-related actions. Results: The study identified the causes of under-five defaulting and the zero-dose gap, i.e., the inadequate support of local community leaders in under-five vaccination sensitization and surveillance; poor infrastructure to new settlement areas; hesitancy and unwillingness of parents/guardians; absence of house numbers; limited/time-constrained availability of resources to facilitate mobile immunization services, etc. The participants were able to come up with 309 ideas, which were refined through multiple iterations using the impact–-effort matrix and skimmed down to three (3) solutions: (i) having health facilities to notify and alert local leaders about vaccination dates; (ii) using parents, kids, and grownups who got vaccinated to influence others; (iii) using local government leaders and house representatives for vaccine advocacy. Of these, the solution involving local government leaders and house representatives for vaccine advocacy was implemented. An advocacy strategy was used to enhance the collaboration of the District Commissioner, Council leaders, and community leaders. A home-to-home interpersonal sensitization approach accompanied by the household delivery of vaccination services was employed. The findings reveal that the HCD framework was impactful in increasing collaborations/cooperation with local government leaders and community ownership of the under-five vaccination initiative. As a result, 67,145 houses, equal to 104%, were reached, surpassing the initial target of 64,800 houses, and 131,088 families, equal to 83% of the targeted 156,995 households, were sensitized through a home-to-home campaign approach. This study demonstrates the effectiveness of the approach. Researchers and practitioners are encouraged to adopt the HCD approach when addressing public health challenges, especially in complex sociocultural settings.